2020
DOI: 10.1002/alz.042132
|View full text |Cite
|
Sign up to set email alerts
|

Vortioxetine use in demented patients

Abstract: Background Vortioxetine is a new antidepressant with a distinctive pharmacological profile. It combines inhibition of serotinine transporter with modulation of various serotonine receptors. Its cognitive benefit in adults depressed patients has been previously demonstrated. There is evidence of its antidepressant effect in the elderly but not specifically of its utiliity in demented population. Effects in a group of different types of dementia patients are showed and hypothesis of its efficacy based on its pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Vortioxetine treatment was associated with significant improvements in cognitive function in an open-label study in community-dwelling older adults with mild cognitive impairment ( Tan and Tan, 2021 ). A small retrospective cohort study has also demonstrated improvements in behavioral and psychological symptoms of dementia during treatment with vortioxetine ( Valverde et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Vortioxetine treatment was associated with significant improvements in cognitive function in an open-label study in community-dwelling older adults with mild cognitive impairment ( Tan and Tan, 2021 ). A small retrospective cohort study has also demonstrated improvements in behavioral and psychological symptoms of dementia during treatment with vortioxetine ( Valverde et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%